2013
DOI: 10.7869/tg.118
|View full text |Cite
|
Sign up to set email alerts
|

Profile of patients with incidentally detected nonalcoholic fatty liver disease (IDNAFLD) in coastal eastern India

Abstract: In India, incidentally detected NAFLD (IDNAFLD) patients are predominantly middle aged males, most of whom are not lean. Most of these patients seek consultation for functional bowel disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 44 publications
3
20
0
1
Order By: Relevance
“…The outcome well-matched with the studies of Duseja A and Singh SP et al where in the highest prevalence is seen among patients with BMI > 25 10,19 . This study is consistent with Amarapurkar D et al, Alam S et al, Singh SP et al, Somalwar AM et al and Hu X et al 13,14,23,24,25 Effect on Subjective Parameters Anorexia: In this study assessing anorexia before and after the treatment at various assessment days, it was found that, 7(35%) patients had mild anorexia, 1(5%) patient had moderate anorexia, 12 (60%) patients had no anorexia at baseline in group-A while 9 (45%) patients had mild anorexia, 1 (5%) patient had moderate anorexia, and 10 (50%) patients had no anorexia at baseline in group-B. After administration of Dawaul-Kurkum in group A and administration of placebo in group-B, at 60 th day, it was observed that anorexia was not present in any patients in group-A, while no improvement was found in group-B.…”
Section: Resultssupporting
confidence: 91%
“…The outcome well-matched with the studies of Duseja A and Singh SP et al where in the highest prevalence is seen among patients with BMI > 25 10,19 . This study is consistent with Amarapurkar D et al, Alam S et al, Singh SP et al, Somalwar AM et al and Hu X et al 13,14,23,24,25 Effect on Subjective Parameters Anorexia: In this study assessing anorexia before and after the treatment at various assessment days, it was found that, 7(35%) patients had mild anorexia, 1(5%) patient had moderate anorexia, 12 (60%) patients had no anorexia at baseline in group-A while 9 (45%) patients had mild anorexia, 1 (5%) patient had moderate anorexia, and 10 (50%) patients had no anorexia at baseline in group-B. After administration of Dawaul-Kurkum in group A and administration of placebo in group-B, at 60 th day, it was observed that anorexia was not present in any patients in group-A, while no improvement was found in group-B.…”
Section: Resultssupporting
confidence: 91%
“…20 In another study from costal eastern India, one fourth of patients had evidence of NASH on liver biopsy on presentation. 21 In another Asian study involving 52 patients, biopsy proven NASH at presentation was found in 32.6% patients while 23% patients with baseline NAFL progressed to NASH. 22 In contrast, a recent study from the West with mean 6.6 years follow up, baseline NASH was found in 75% patients with disease progression from NAFL to NASH in 44% patients.…”
mentioning
confidence: 95%
“…In this study, 29% had lean NAFLD and 72% were overweight or obese [13]. In another study from our region, a significant proportion of NAFLD patients [16%] had normal BMI (lean body weight, BMI<23 kg/m 2 ) [14]. However studies from the West consistently employ BMI<25kg/m 2 as cut off for lean NAFLD [15][16][17][18][19].…”
Section: Definition Of Lean Nash and Justificationmentioning
confidence: 74%